Comparative Studies of Palmatine with Metformin and Glimepiride on the Modulation of Insulin Dependent Signaling Pathway In Vitro, In Vivo & Ex Vivo - Okechukwu Patrick Nwabueze; Mridula Sharma; Abbirami Balachandran; Anand Gaurav; Anis Najwa Abdul Rani; Jeleń Małgorzata; Morak-Młodawska Beata; Charlie A. Lavilla; Merell P. Billacura (Pharmaceuticals, 2022)
(1) Insulin resistance, a symptom of type 2 diabetes mellitus (T2DM), is caused by the inactivation of the insulin signaling pathway, which includes IRS-PI3K-IRS-1-PKC-AKT2 and GLUT4. Metformin (biguanide) and glimepiride (sulfonylurea) are both drugs that are derivatives of urea, and they are widely used as first-line drugs for the treatment of type 2 diabetes mellitus. Palmatine has been previously reported to possess antidiabetic and antioxidant properties. (2) The current study compared palmatine to metformin and glimepiride in a type 2 diabetes model for ADME and insulin resistance via the PI3K/Akt/GLUT4 signaling pathway: in vitro, in vivo, ex vivo, and in silico molecular docking. (3) Methods: Differentiated L6 skeletal muscle cells and soleus muscle tissue were incubated in standard tissue culture media supplemented with high insulin and high glucose as a cellular model of insulin resistance, whilst streptozotocin (STZ)-induced Sprague Dawley rats were used as the diabetic model. The cells/tissue/animals were treated with palmatine, while glimepiride and metformin were used as standard drugs. The differential gene expression of PI3K, IRS-1, PKC-α, AKT2, and GLUT4 was evaluated using qPCR. (4) Results: The results revealed that the genes IRS-PI3K-IRS-1-PKC-AKT2 were significantly down-regulated, whilst PKC-α was upregulated significantly in both insulin-resistant cells and tissue animals. Interestingly, palmatine-treated cells/tissue/animals were able to reverse these effects. (5) Conclusions: Palmatine appears to have rejuvenated the impaired insulin signaling pathway through upregulation of the gene expression of IRS-1, PI3K, AKT2, and GLUT4 and downregulation of PKC-expression, according to in vitro, in vivo, and ex vivo studies.